CAMPUR KODE DAN ALIH KODE DALAM LIRIK LAGU “SENANDUNG RINDU” SYUBBANUL MUSLIMIN PERSPEKTIF SOSIOLINGUISTIK - Malyuna Milyari Faidah (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
This research about code mixing and code switching in sociolinguistic studies. The analysis of code mixing and code switching was carried out throught the lyrics of the song “Senandung Rindu” by the Syubbanul Muslimin, rebana vocal group. The background of code code mixing and code switching in the lyrics of the song because Indonesian people have bilingual or multilingual. They are able to use two or more different languages when interacting wich each other. This research was conducted with a descriptive qualitative research method. The method of data collection by recording, free listening, recording, and data recapitulation techniques. The result of this research are : there are eight code mixing that found in the lyrics of the song “Senandung Rindu”, the form is outer code mixing and also of alternation, that found one form of clause code mixing and the other of a phrase, there are six code switching that found in the song’s lyrics and the form is internal code switching.